Estimating maximal aerobic speed in academy soccer players: A comparison between time trial methods and the 30-15 intermittent fitness test - Smith, K.; Wright, M. D.; Chesterton, P.; Taylor, J. M. (European Journal of Sport Science, 2025)
Aerobic fitness is crucial to team sport performance and can be practically estimated through field-based assessments of maximal aerobic speed (MAS) in soccer players. However, method comparisons are underexplored. This study compared MAS estimation via a 6-min distance trial (6minDT), 1800-m time trial (1800mTT) and 30-15 intermittent fitness test (30-15IFT) and qualitative preferences in academy soccer players. Twenty-six male players (age: 17.2 ± 0.6 years; stature: 178.4 ± 5.1 cm; body mass: 71.8 ± 7.7 kg) completed a 30-15IFT, 6minDT and 1800mTT in a counterbalanced order. Total distance was measured via 10 Hz global positioning system units, with MAS defined as 87% of 30-15IFT finishing speed (vIFT) and distance divided by time to completion for the 6minDT and 1800mTT. Pearson's correlations calculated associations between MAS estimates, and a robust repeated measures ANOVA estimated marginal mean differences between tests. A very large association was observed between performance in the 1800mTT and 6minDT (r = 0.72; 95% confidence interval, 0.46 to 0.86). Large associations were observed between the 30-15IFT and 6minDT and 1800mTT (6minDT: r = 0.65; 0.35 to 0.83; 1800mTT: 0.66, 0.37 to 0.84), respectively. MAS estimated from the 30-15IFT was significantly higher than the 6minDT (0.57, 0.50 to 0.65 m·s-1, p < 0.0001) and 1800mTT (0.45, 0.37 to 0.52 m·s-1, p < 0.0001). MAS estimated from the 6minDT was lower than the 1800mTT (-0.13, -0.21 to -0.05 m·s-1, p = 0.0002). In conclusion, although associations between 6minDT-, 1800mTT- and 30-15IFT-derived MAS exist, all tests provide distinct estimations of MAS.